2021
DOI: 10.1016/j.jcmgh.2021.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Macrophages in Gastrointestinal Homeostasis: Heterogeneity and Implications in Disease

Abstract: Intestinal macrophages are the most abundant immune cells in our gut but understanding of their function is impeded by their heterogeneity. In this review we dissect different subtypes of intestinal macrophages and highlight their roles in several gastrointestinal (GI) disorders.Intestinal macrophages play a key role in the gut immune system and the regulation of gastrointestinal physiology, including gut motility and secretion. Their ability to keep the gut from chronic inflammation despite constantly facing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 154 publications
1
37
0
Order By: Relevance
“…Better understanding of the subpopulations of macrophages and their changes in maintaining endostasis is in great need. 34–36 Our fluorescence assays in the droplets have revealed that the different levels of extracellular secretion of NO by individual macrophages might be associated with the cellular heterogeneous properties. In the literature, the reports on detecting extracellular secretion of NO are few.…”
Section: Discussionmentioning
confidence: 99%
“…Better understanding of the subpopulations of macrophages and their changes in maintaining endostasis is in great need. 34–36 Our fluorescence assays in the droplets have revealed that the different levels of extracellular secretion of NO by individual macrophages might be associated with the cellular heterogeneous properties. In the literature, the reports on detecting extracellular secretion of NO are few.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract harbors copious amounts of tissue macrophages, orchestrating innate and adaptive immune systems, helping to maintain homeostasis via tolerance to commensal microbes, as well as resisting potentially harmful pathogens ( Yip et al, 2021 ). In the past, the origin of tissue macrophages was considered to be the blood monocytes, deriving from precursors in the bone marrow ( van Furth et al, 1972 ; Bain and Mowat, 2014 ).…”
Section: Origin and Maintenance Of Intestinal Macrophagesmentioning
confidence: 99%
“…4). 10,11,[111][112][113][114][115][116][117] These MMs lie in close proximity to neurons within the myenteric plexus, circular and longitudinal smooth muscle layers, and interstitial cells of Cajal. 111 MMs exist in different subsets based on their morphological (stellate and bipolar) structure, however their precise role is still ambiguous.…”
Section: Muscularis Macrophage Activation and Initiation Of Intracell...mentioning
confidence: 99%